Patient satisfaction in regional referral hospitals of Bhutan: Insights from a cross-sectional study - Kuenzang Dorji; Kinga Jamphel; Jigme Kelzang; Ugyen Pelmo; Hem Kumar Nepal; Sonam Zangpo; Sonam Wangdi; Karma Galey (PLoS ONE, 2025)
Background Patient satisfaction is crucial for evaluating healthcare quality and guiding continuous quality improvement. Globally, patient satisfaction has been extensively studied; however, there is limited research on this topic in Bhutan, where the healthcare system is in the early stages of developing a quality-oriented culture. To address this gap, we aimed to evaluate patient satisfaction levels among different socio-demographic and clinical groups and identify the predictors of patient satisfaction in Bhutan. Methods We conducted a retrospective analysis of patient satisfaction survey responses archived in the quality assurance unit of two tertiary healthcare centres in Bhutan: Mongar Eastern Regional Referral Hospital and Gelephu Central Regional Referral Hospital. The routine surveys, administered throughout April 2024, utilised an adapted version of the Patient Satisfaction Questionnaire-18. The data were analysed using descriptive and inferential statistics. Results Our study revealed significant variations in patient satisfaction across socio-demographic and clinical groups. Ethnicity (P-value = 0.017), occupation (P-value = 0.014), and education level (P-value = 0.021) emerged as significant predictors of satisfaction. Sharchop and other ethnic groups (P-value= < 0.001); farmers, religious personnel, and other occupational groups (P-value= < 0.001); and illiterate (P-value= < 0.001) individuals exhibited significantly higher satisfaction levels. While patient type (P-value = 0.472), age (P-value = 0.553), and marital status (P-value = 0.448) influenced satisfaction levels, they did not emerge as significant predictors when considering other variables. Overall, patient satisfaction in Bhutan is 4.06 on a 5-point Likert scale. Satisfaction is highest in the financial domain, while accessibility and convenience received the lowest scores. Conclusions Overall, with a score of 4.06 on a 5-point Likert scale, patient satisfaction in Bhutan is high. However, our findings highlight the need to address socio-demographic disparities in patient satisfaction. As the Bhutanese socio-demographic landscape evolves, satisfaction levels may decline. To enhance overall satisfaction, healthcare policymakers should focus on improving accessibility and convenience. Strategies such as establishing dynamic limits on free services, exploring private sector engagement in advanced healthcare service, and strengthening the healthcare workforce are essential for sustainable and quality healthcare service delivery.